Spatial Stigma and Health in Postindustrial Detroit. (January 2016) - Graham, Louis F.; Padilla, Mark B.; Lopez, William D.; Stern, Alexandra M.; Peterson, Jerry; Keene, Danya E.
An emerging body of research suggests that those who reside in socially and economically marginalized places may be marked by a stigma of place, referred to as spatial stigma, which influences their sense of self, their daily experiences, and their relations with outsiders. Researchers conducted 60 semistructured interviews at partnering community-based organizations during summer 2011 with African American and Latina/o, structurally disadvantaged youth of diverse gender and sexual identities who were between 18 and 26 years of age residing in Detroit, Michigan. The disadvantaged structural conditions and dilapidated built environment were common themes in participants' narratives. Beyond these descriptions, participants' framings and expressions of their experiences in and perceptions of these spaces alluded to reputational qualities of their city and particular areas of their city that appear related to spatial stigma. Young Detroit residents articulated the ways that they experience and navigate the symbolic degradation of their city.